Synthesis, characterization, and optimization of antimicrobial biolubricant derived from Ocimum lamiifolium and lactic acid - Dereje Ayele Gebreyes; Melakuu Tesfaye Alemea; Alemu Gonfa Robi; Workiye Getnet Abera; Getachew Alemu Tenkolu (Heliyon)
Optimal extraction parameters were determined, yielding 12.4 % oil at 4.5 h, with a particle size of 1.375 mm and a solute-to-solvent ratio of 0.28 w/v. The extracted oil exhibited high yield (15 % moisture, 0.92 g/mL specific gravity), a volatile lubricant component (3 %), a pH of 4.2–5.91, low ash (11.5 %), high saponification value (19.7 g KOH/g) and moderate acid number (8.9 mg KOH/g), iodine value of 35.3 g/L, low viscosity (0.1160 Pa s), and high diffusion capacity (95 %). Chemical analysis using UV–Vis spectrophotometry was employed to identify the constituents present in the extract, while FTIR spectra indicated the presence of alcoholic and phenolic components, suggesting interactions with lactic acid. Through GC/MS analysis, a total of 32 phytochemicals were identified, with seven significant ones: Eugenol (Phenol), Isocaryophyllene, Elemicin (benzene), Hexadecanoic acid with methyl ester, Octadecanoic acid with methyl ester, Neophytadiene and Squalene. Evaluation against E. coli, B. subtilis, S. typhimurium, and S. aureus revealed the O. lamiifolium extract and biolubricants most active against S. aureus and E. coli, suggesting potential for superior antibacterial lubricants with this plant extract and lactic acid.